2015
DOI: 10.3906/tar-1501-25
|View full text |Cite
|
Sign up to set email alerts
|

Influences of different iron levels on plant growth and photosynthesis of W. Murcott mandarin grafted on two rootstocks under high pH conditions

Abstract: W. Murcott scion, budded onto two rootstocks, was evaluated under high pH conditions supplied with different Fe levels. Plant dry weight, leaf area, iron chlorosis symptom scale, leaf chlorophyll concentration, net photosynthetic rate, and ferric-chelate reductase (FCR) activity variables were investigated under high pH conditions. Control plants (T1) produced the most leaf area, whereas plants grown without Fe (T2) produced the least. Dry weight was highest in 'Volkameriana' T1 (control) plants and lowest in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…La variable de SST mostró diferencias altamente significativas (p≤ 0.05), donde los tratamientos con 550 g de Fe mostraron los mayores valores de grados Brix con 5.38 (Cuadro 5). El área foliar (AF) del cultivo de jitomate en ambas dosis de Fe se vieron afectadas significativamente, con una mayor área foliar en las dosis altas, superando al testigo en 138%, presentando un área foliar promedio de 2 917 cm 2 , esto fue debido a que la baja concentración de Fe provocó una disminución en los contenidos de clorofila y otros componentes de los cloroplastos lo que disminuyó la capacidad de crecimiento del cultivo, resultados similares fueron encontrados por Incesu et al (2015) en el cultivo de Mandarina; sin embargo, en las diferentes dosis de Zn y Cu fueron estadísticamente similares al testigo (p≤ 0.05) Para las dosis de Zn, el testigo mostró una mayor área foliar seguido de las concentraciones altas, datos contrastantes fueron reportados por Haleema y Hussain (2018) en cultivo de jitomate quienes demostraron que a mayor dosis de Zn mayor fue el área foliar. En Cu se observó que las dosis altas superaron al testigo 63% (Figura 1), dichos resultados contradicen a lo mencionado por Yruela (2005), quien menciona que las plantas con exceso de Cu regularmente presentan una disminución en la biomasa.…”
Section: Resultados Y Discusiónunclassified
“…La variable de SST mostró diferencias altamente significativas (p≤ 0.05), donde los tratamientos con 550 g de Fe mostraron los mayores valores de grados Brix con 5.38 (Cuadro 5). El área foliar (AF) del cultivo de jitomate en ambas dosis de Fe se vieron afectadas significativamente, con una mayor área foliar en las dosis altas, superando al testigo en 138%, presentando un área foliar promedio de 2 917 cm 2 , esto fue debido a que la baja concentración de Fe provocó una disminución en los contenidos de clorofila y otros componentes de los cloroplastos lo que disminuyó la capacidad de crecimiento del cultivo, resultados similares fueron encontrados por Incesu et al (2015) en el cultivo de Mandarina; sin embargo, en las diferentes dosis de Zn y Cu fueron estadísticamente similares al testigo (p≤ 0.05) Para las dosis de Zn, el testigo mostró una mayor área foliar seguido de las concentraciones altas, datos contrastantes fueron reportados por Haleema y Hussain (2018) en cultivo de jitomate quienes demostraron que a mayor dosis de Zn mayor fue el área foliar. En Cu se observó que las dosis altas superaron al testigo 63% (Figura 1), dichos resultados contradicen a lo mencionado por Yruela (2005), quien menciona que las plantas con exceso de Cu regularmente presentan una disminución en la biomasa.…”
Section: Resultados Y Discusiónunclassified
“…Exogenously applied Fe in both forms (Fe-Asp and FeSO 4 ) was found to be effective in ameliorating the adverse impacts of imposed drought stress on the biosynthesis of leaf photosynthetic pigments by decreasing membrane lipid peroxidation that might have improved the leaf photosynthetic efficiency with better growth and yield of water stressed sunflower plants. Previous studies have also reported that the exogenous Fe application improved the stress tolerance by boosting up the plant photosynthetic efficiency of maize [76], sunflower [77] and W. murcott mandarin [78]. Furthermore, it was reported by Sadak et al [78] that foliary-applied Asp increased the stress tolerance of Vicia faba plants associated with improved accumulation of phenolic content, proline, amino acids, total soluble sugars, polyamines, and IAA [79].…”
Section: Role Of Leaf Photosynthetic Pigmentsmentioning
confidence: 97%
“…Previous studies have also reported that the exogenous Fe application improved the stress tolerance by boosting up the plant photosynthetic efficiency of maize [76], sunflower [77] and W. murcott mandarin [78]. Furthermore, it was reported by Sadak et al [78] that foliary-applied Asp increased the stress tolerance of Vicia faba plants associated with improved accumulation of phenolic content, proline, amino acids, total soluble sugars, polyamines, and IAA [79]. In rice plants (20 mg kg −1 ), foliar spray of Asp improved the leaf photosynthetic pigments that lead to better plant growth under stressful environment [32].…”
Section: Role Of Leaf Photosynthetic Pigmentsmentioning
confidence: 99%
“…Iron (Fe) is the fourth most abundant element in the earth’s crust, at 5%, and the soil contains from 1 to 5% (on average 3.2%) Fe. On the other hand, the Fe content in plants is normally only 0.005% [ 6 , 7 ]. Fe is an important elemental nutrient for plants; it not only participates in the synthesis of organelles, such as the chloroplast, mitochondria, and palisade tissues, but also acts as a cofactor for numerous enzymatic processes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%